United States, sled dogs barking in Utqiaġvik - Sorensen, Clarence Woodrow, 1907-1982; Harris, Eugene V., 1913-1978 (1959)
Dog standing on rear legs barking while tied to chain. Grayscale Sorensen Safety Negatives, Binder: North & Central America 3